UMP-Adabi collaboration distributes 600 sahur meals for students - Mimi Rabita, Abdul Wahit (2023)
KUANTAN, 6 April 2023 - Universiti Malaysia Pahang (UMP) and Adabi Consumer Industries Sdn. Bhd. (Adabi) continued the Ramadan 2023 programme by approaching students in the Sahur Jangan Tak Sahur Programme.